Rapid screening of novel tyrosinase inhibitory peptides from a pearl shell meat hydrolysate by molecular docking and the anti-melanin mechanism. Issue 3 (17th January 2023) - Huang, Pantian; Miao, Jianyin; Liao, Wanwen; Huang, Congshu; Chen, Bingbing; Li, Yingkun; Wang, Xianghua; Yu, Yan; Liang, Xingtang; Zhao, Haishan; Cao, Yong
Abstract : The tyrosinase inhibitory peptides screened from pearl shell meat hydrolysate can effectively inhibit tyrosinase activity and reduce melanin content. Abstract : Pearls are an edible and medicinal resource with whitening activity and nutritional value in China. In the previous study, we found that the pearl shell meat hydrolysate showed dual activities of antioxidation and tyrosinase inhibition, which were similar to the activities of pearls. In this research, a pearl shell meat hydrolysate was isolated, identified and screened by molecular docking, and three peptides FLF, SPSSS and WLL with high tyrosinase inhibitory activities were obtained. The results indicated that FLF, SPSSS and WLL could effectively inhibit tyrosinase activities and the inhibition rates (1.0 mg mL −1 ) were 54.32%, 65.26% and 57.50%, respectively. The results of a zebrafish whitening experiment showed that the tyrosinase activities of zebrafish treated with FLF, SPSSS and WLL decreased by 75.41%, 62.87% and 64.99% ( p < 0.05), respectively, and the melanin content decreased by 37.34%, 38.52% and 40.39% ( p < 0.05), respectively. In a B16F10 cell whitening experiment, compared with a control group, FLF, SPSSS and WLL also showed a significant whitening effect, the tyrosinase activities decreased by 84.08%, 79.08% and 77.45% ( p < 0.05), respectively, and the melanin content decreased by 42.23%, 34.37% and 34.02% ( p < 0.05), respectively. Moreover, the active peptides could act on three signal pathways including Wnt/β-catenin, MAPK and MC1R/α-MSH and significantly downregulated the expressions of the signaling factors WNT4, MITF, β-catenin, ERK, JNK, TRP1 and TRP2 ( p < 0.05). The results demonstrated that the whitening active peptides were edible natural antioxidants, tyrosinase inhibitors and skin anti-melanin agents, which could be added to functional foods as food ingredients.